Extraction of Natural Antioxidant from Local Sorghum Brown Variety and Its Activity Enhancement by Germination and Microwave - Nisa, Fithri Choirun (Fakultas Teknologi Pertanian Universitas Brawijaya, 2010)
Brown sorghum was reported as a source of antioxidants such as phenolic, tannin, anthocyanin. This research was designed into 2 steps. The first step was aimed to find out the best type of solvent (methanol, ethanol, and acetone) for antioxidant extraction in each fraction (milled grain and bran) of sorghum. The aim of the second step was to observe the effect of germination and microwave on antioxidant activity. Nested design was used in the first step. The results of the first step showed that best treatment in milled grain was obtained from ethanol with phenolic content of 100,28 mg/g, anthocyanin content of 28.34 ppm, tocopherol content of 2.24 mg/mL, antioxidant activity of 95.96%, and yield of 10.105%. The best treatment in bran was obtained from methanol with phenolic content of 89.74 mg/g, anthocyanin content of 50.70 ppm, tocopherol content of 10.55 mg/mL, antioxidant activity of 97.15%, and yield of Â 9.02%. The results of the second step research showed that germination has significantly affected (Î±=0.05) antioxidant activity and yield extract. The extract was characterized by phenolic content of 108.67 mg/g, anthocyanin content of 35.80 ppm, tocopherol content of 2.97 mg/mL, antioxidant activity of 98.00%, and yield of Â 16.94%. While microwave had significantly affected (Î±=0.05) tocopherol content, antioxidant activity, and yield extract. The characteristics of product were phenolic content of 113.71 mg/g, anthocyanin content of 48.68 ppm, tocopherol content of 17.40 mg/mL extract, antioxidant activity of 98.71%, and yield of Â 12.47%.Keywords: brown sorghum, natural antioxidant, microwave